Penyelenggaraan Layanan Kependudukan dan Catatan Sipil di Mall Pelayanan Publik Kabupaten Sleman - Muhammad Afrizal B; Ashar Abdillah; Seno Wibowo; Willem Sedik (CV. Ulil Albab Corp, 2023)
This study aims to describe the implementation of the Sleman Regency Public Service Mall at the Dukcapil Service counter using the Total Quality Management (TQM) Theory concept approach. As for this research, it uses a qualitative descriptive approach. Data were obtained from the results of this study through observing the implementation of the Sleman Regency Public Service Mall, especially at the Dukcapil service counters. The results of the study that emerged showed that in the implementation of Dukcapil services at MPP Sleman, namely (1) MCH Application Services (Child Identity Cards), (2) Online registration information services; (3) KTP and KIA printing services through independent pavilion machines that have registered online. This article tries to analyze the Total Quality Management concept approach in the delivery of services at the Sleman Public Service Mall. TQM is a concept in the Sleman Public Service Mall. In the TQM concept, namely seeking to focus on customer engagement, involvement and empowerment, strengthening human resources through education and training, continuous improvement. If we compare it with the TQM approach, self-organization is not maximized. If we examine the information from MPP officers at the Disdukcapil counter, the service itself is limited and the service is held only once a week, namely on Thursday. When we break down from the explanation of the concept of TQM, the focus is on customer service in an effort to improve excellent service to customers or in this case to the community.